Induced mutations by gamma ray irradiation to Argomulyo soybean (Glycine max) variety - DIANA SOFIA HANAFIAH; TRIKOESOEMONINGTYAS TRIKOESOEMONINGTYAS; SUDIRMAN YAHYA; DESTA WIRNAS (Smujo International, 2010)
Abstract. Hanafiah DS, Trikoesoemaningtyas, Yahya S, Wirnas D. 2010. Induced mutations by gamma-ray irradiation to Argomulyo soybean (Glycine max) variety. Nusantara Bioscience 2: 121-125. Induced mutation by gamma-ray irradiation is one way to increase genetic variability of plants. This research used gamma-ray irradiation on low doses (micro mutation). The aim of this research was to know the response of doses level by micro mutation on gamma-ray irridation to the growing and development of Argomulyo variety of soybean [Glycine max (L) Merr]. The seeds were irradiated by gamma-ray micro mutation doses, namely 0 gray, 50 gray, 100 gray, 150 gray, and 200 gray. Variations that were obtained of each character at generation M1 and M2 influences plants growth and development either through qualitative and quantitative that finally will influence plant’s production. The average highest genetic variation at M2 generation of soybean was on 200 Gray doses. Results of the research indicated that gamma-ray irradiation on 200 Gray doses effectively caused by plant variation genetic.